DISSOLUTION OF PRIMARY MINERALS OF BASALT IN NATURAL WATERS I. CALCULATION OF MINERAL SOLUBILITIES FROM 0°C TO 350°C - Stefánsson A. (My University, 2001)
The solubilities of forsterite, fayalite, enstatite, ferrosilite, hedenbergite, diopside, anorthite, high-albite, magnetite, hematite, ulvöspinel, ilmenite, F-apatite and OH-apatite and olivine, plagioclase, orthopyroxene, clinopyroxene and Fe–Ti oxide solid solutions of fixed composition were calculated in the temperature range 0–350°C at saturated water vapour pressure. The thermodynamic database used for end-member minerals was that of Robie and Hemingway [Robie, R.A., Hemingway, B.S., 1995. Thermodynamic properties of minerals and related substances at 298.15 K and 1 bar (105 Pascals) pressures and at higher temperatures. U.S. Geol. Surv. Bull. 2131, 461 pp.] except for plagioclases [Arnórsson, S., Stefánsson, A., 1999. Assessment of feldspar solubility constants in water in the range of 0° to 350°C at vapor saturation pressures. Am. J. Sci. 299, 173–209.] and that of Shock and Helgeson [Shock, E.L., Helgeson, H.C., 1988. Calculation of the thermodynamic and transport properties of aqueous species at high pressures and temperatures: correlation algorithms for ionic species and equation-of-state predictions to 5 kb and 1000°C. Geochim. Cosmochim. Acta 53, 2009–2036.] and Shock et al. [Shock, E.L., Oelkers, E.H., Johnson, J.W., Sverjensky, D.A., Helgeson, H.C., 1992. Calculation of the thermodynamic properties of aqueous species at high pressures and temperatures: effective electrostatic radii, dissociation constants, and standard partial molal properties to 1000°C and 5 kbar. J. Chem. Soc., Faraday Trans. 88, 803–826.] for most aqueous species. For aqueous Fe(OH)4− and Al(OH)4−, the thermodynamic properties reported by Diakonov et al. and Pokrovskii and Helgeson [Pokrovskii, V.A., Helgeson, H.C., 1995. Thermodynamic properties of aqueous species and the solubilities of minerals at high pressures and temperatures: the system Al2O3–H2O–NaCl. Am. J. Sci. 295, 1255–1342], respectively, were used. In the present study, the standard partial molal properties and the HKF equation-of-state parameters for aqueous H4SiO40 were revised to better describe the recent experimental results at low temperatures. For H4SiO40, the new parameters are also consistent with quartz solubility experiments up to 900°C and 5 kbar. Further, the HKF equation-of-state parameters for aqueous Ti(OH)40 were estimated from rutile solubility [Ziemniak, S.E., Jones, M.E., Combs, K.E.S., 1993. Solubility behaviour of titanium (IV) oxide in alkaline media at elevated temperatures. J. Sol. Chem. 22, 601–623.], which enables the calculations of the solubility of Ti-bearing minerals at elevated temperatures and pressures. Much higher solubilities were found for the silicate minerals below 100°C than previously reported, which is related to higher quartz solubility at low temperature and correspondingly new data on the thermodynamic properties of H4SiO40. The present results are particularly important for the stabilities of primary basaltic minerals of natural composition under weathering conditions. They are also of importance for the study of equilibrium/dis-equilibrium conditions in active geothermal systems.